Fish otoliths from the early Miocene of Chile: a window into the evolution of marine bony fishes in the Southeast Pacific - Werner W. Schwarzhans; Sven N. Nielsen (Swiss Journal of Palaeontology)
Abstract Few fossil fish otolith associations have been described from the Pacific side of the Americas and, except for a single species (Steindachneria svennielseni), none have been described from Pacific South America south of the Central American tropical region. Here, we describe a rich otolith assemblage obtained from fifteen early Miocene outcrop locations along the Chilean coast from about 33°S to about 45°S. More than 2,000 specimens were studied resulting in the recognition of 67 species, with 27 being new to science. This assemblage represents an important new data point distant from any previously known otolith-based fish fauna, with the nearest coeval associations being from the Caribbean Province in Venezuela, which lies about 5000 km to the north, and New Zealand, which is about 9000 km to the west. The fauna represents a mixture of offshore and shallow water fishes and is rich in myctophids, paralichthyids (Citharichthys), ophidiids (Lepophidium), steindachneriids, and macrourids. Typical tropical American fishes are nearly completely absent, with the exception of Steindachneria and certain anguilliforms. The mesopelagic faunal component, chiefly Myctophidae, shows a striking resemblance to the well-known coeval fish fauna from New Zealand, and both are interpreted as representing an early South Pacific mesopelagic bioprovince. The strong correlation with the mesopelagic otolith-based fish fauna from New Zealand constricts the time interval of the sampled sediments to the middle Burdigalian (approximately 17.5 to 18.5 Ma). All otoliths obtained from the early Miocene of Chile relate to extant fish groups of the area and few exotic components not currently present in the East Pacific. The sole exception is a morpho-type described as Navidadichthys which has an unresolved relationship, possibly with the Prototroctidae, a family that is today endemic to the freshwater and nearshore marine environments of Australia and New Zealand. The new taxa are in the sequence of taxonomic description: Pterothrissus transpacificus n. sp., Pythonichthys panulus n. sp., Chiloconger chilensis n. sp., Gnathophis quinzoi n.sp., Rhynchoconger chiloensis n. sp., Navidadichthys mirus n. gen. et n. sp., Maurolicus brevirostris n. sp., Polyipnus bandeli n. sp., Lampanyctus ipunensis n. sp., Physiculus pichi n. sp., Coelorinchus fidelis n. sp., Coelorinchus rapelanus n. sp., Nezumia epuge n. sp., Paracarapus chilensis n. gen. et n. sp., Lepophidium chonorum n. sp., Lepophidium mapucheorum n. sp., Sirembola supersa n. sp., Spectrunculus sparsus n. sp., Pseudonus humilis n. sp., Capromimus undulatus n. sp., Agonopsis cume n. sp., Cottunculus primaevus n. sp., Kuhlia orientalis n. sp., Citharichthys parvisulcus n. sp., Citharichthys vergens n. sp., Achirus australis n. sp., Achirus chungkuz n. sp. ZooBank LSID: urn:lsid:zoobank.org:pub:38A10A21-ECAA-4BBE-BF9B-3D9204B69CA4 https://zoobank.org/B0213E37-6E6F-445B-9B2B-B03494659964 .